Effect of geocomposite reinforcement on the performance of thin asphalt pavements: Accelerated pavement testing and laboratory analysis - Lorenzo Paolo Ingrassia; Amedeo Virgili; Francesco Canestrari (Case Studies in Construction Materials, 2020)
The objective of this study is to assess the effect of geocomposite reinforcement on fatigue cracking, reflective cracking and permanent deformation accumulation of thin asphalt pavements. For this purpose, a full-scale trial section was constructed with different interfaces: unreinforced (reference) and reinforced with three types of geocomposites, formed by the combination of a bituminous membrane with a fabric or grid. The experimental program included accelerated pavement testing (APT) carried out by means of Fast Falling Weight Deflectometer (FastFWD) and laboratory tests (three point bending tests) on samples taken from the trial section. After APT, significant permanent deflections were observed, likely due to the plastic yielding of the unbound layers. Nevertheless, all the geocomposites improved the permanent deformation resistance as compared to the unreinforced pavement by reducing the vertical strain at the top of the subgrade. Moreover, the geocomposites increased the energy necessary for the crack propagation by three to eight times with respect to the unreinforced pavement. Overall, these findings indicate that the use of geocomposites can extend the service life of thin asphalt pavements in terms of both cracking and permanent deformation accumulation.